2015
DOI: 10.1159/000431089
|View full text |Cite
|
Sign up to set email alerts
|

Use of Observational Periods or Ancillary Tests in the Determination of Brain Death in Germany

Abstract: Background: In the absence of primary infratentorial brain lesions, the German guideline on brain death (BD) permits diagnosis based on two clinical assessments separated by a defined observational period or by one clinical assessment and an ancillary test. Methods: Retrospective analysis of patients fulfilling the clinical criteria of BD registered with the organ procurement organization of northeastern Germany during a 10-year period. Results: 2,745 patients were included. Compared to clinical observations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 14 publications
(22 reference statements)
0
23
1
3
Order By: Relevance
“…For instance, these tests could prove particularly useful for patients with isolated brainstem injury who undergo ancillary testing for clinical indications (e.g., confounders to clinical examination) or because of legal regulations (e.g., Germany requires ancillary testing for all patients who are suspected of BD/DNC due to an infratentorial lesion). 20 As noted previously, there is evidence that supratentorial blood flow can persist in patients that fulfill all clinical criteria for BD/DNC and have absent brainstem perfusion on CTP. 13 Based on case reports and series, other authors have hypothesized that patients with isolated brainstem death eventually progress to whole-BD because of severe intracranial hypertension from obstructive hydrocephalus, further compounded by the mass effect on the vein of Galen.…”
Section: Implications For the Future Of Ancillary Testing In Bd/dncmentioning
confidence: 66%
See 1 more Smart Citation
“…For instance, these tests could prove particularly useful for patients with isolated brainstem injury who undergo ancillary testing for clinical indications (e.g., confounders to clinical examination) or because of legal regulations (e.g., Germany requires ancillary testing for all patients who are suspected of BD/DNC due to an infratentorial lesion). 20 As noted previously, there is evidence that supratentorial blood flow can persist in patients that fulfill all clinical criteria for BD/DNC and have absent brainstem perfusion on CTP. 13 Based on case reports and series, other authors have hypothesized that patients with isolated brainstem death eventually progress to whole-BD because of severe intracranial hypertension from obstructive hydrocephalus, further compounded by the mass effect on the vein of Galen.…”
Section: Implications For the Future Of Ancillary Testing In Bd/dncmentioning
confidence: 66%
“…Par exemple, ces tests pourraient s’avérer particulièrement utiles pour les patients présentant des lésions cérébrales isolées qui subissent des tests complémentaires pour des indications cliniques (par exemple, des facteurs de confusion à l’examen clinique) ou en raison de règles juridiques (par exemple, l’Allemagne exige des tests complémentaires pour tous les patients soupçonnés de MC/DDN en raison d’une lésion sous-tentorielle). 20 Comme indiqué précédemment, il existe des données probantes selon lesquelles la circulation sanguine supra-tentorielle pourrait persister chez les patients qui remplissent tous les critères cliniques de MC/DDN et pour lesquels aucune perfusion du tronc cérébral n’est visible par tomodensitométrie de perfusion. 13 En se fondant sur des rapports isolés et des séries de cas, d’autres auteurs ont émis l’hypothèse que les patients présentant une mort isolée du tronc cérébral évoluaient par la suite à une mort cérébrale complète en raison de l’hypertension intracrânienne due à une hydrocéphalie non communicante (obstructive), aggravée par l’effet de masse sur la veine de Galien.…”
Section: Implications Pour L’avenir Des Tests Complémentaires Pour Les Diagnostics De Mc/ddnunclassified
“…In the literature, it has been shown that ancillary tests shorten the time to detect brain death. ( 14 ) However, it has been reported in the literature that these ancillary tests may delay the diagnosis of brain death and cause damage to the organ donation target by causing confusion (false negative or false positive findings). ( 15 )…”
Section: Discussionmentioning
confidence: 99%
“…Although ancillary testing, such as electroencephalography (EEG), cerebral angiography, nuclear flow scan, transcranial Doppler, CT angiography and magnetic resonance (MR) angiography, can be utilized in the process of determining BD-due to variability in the interpretation of these studies-it is not a substitute for the clinical examination [67][68][69][70]. In aggregate, the above tests can provide additional data on electrical brain function and cerebral blood flow and "…can be used when uncertainty exist about the reliability of parts of the neurological examination or when the apnea test cannot be performed" [71,72].…”
Section: Brain Death Determinationmentioning
confidence: 99%